Energy Efficiency of Using Hybrid Heating Points in Conditions of Integration of Electrical and Thermal Networks of Urban Neighborhoods. Part 1. Justification of the Feasibility of Using Hybrid Thermal Points - A. V. Sednin; M. I. Pozdnyakova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper discusses the circumstances and technical solutions that contribute to the integration of electrical and thermal networks of urban neighborhoods within the framework of a surplus of electricity generating capacities arising from the imbalance in the development of energy generation and consumption, stochastic processes of market economy development, the transfer of energy-intensive industrial production to other countries, the desire to diversify fuel energy resources, passion for the construction of energy sources for alternative energy resources in counterbalance to traditional energy facilities without taking into account all aspects of the interaction of the former with the environment, etc. With regard to district heating systems of electrical and thermal networks of urban neighborhoods, the use of hybrid heating points is achieved, which, unlike standard solutions, are equipped with electric boilers, thermal accumulators and heat pumps. According to the time of use of generating capacities, preference should be given to options for covering the hot-water load. Based on the average daily load, the power usage time in this case lies in the range of 6000–6500 hours / year. When choosing the capacity of the equipment, it should be borne in mind that the daily load of hot water supply is extremely uneven and also depends on the  day of the week, while the maximum load exceeds the average daily by 2.5 – 3.0 times. When integrating electricity and heat supply systems, it is advisable to consider options for only night-time electricity consumption or night-time consumption plus consumption during the hours of daytime failures of the electricity consumption schedule. If during the new construction the power of the electrical network may vary depending on the selected option, then during the modernization of the heat supply system, the problem is solved if there is a limitation on the available electrical power. Therefore, the definition of these restrictions is a separate issue. In comparison with the direct consumption of electricity for the needs of heat supply, which is a priori energetically and economically inefficient, the use of hybrid systems in heat supply allows us to solve the multifunctional task of increasing the reliability of energy supply and the stability of the functioning of the power system, which is primarily achieved by solving the problem of balancing the capacity of production and energy consumption from the position of aligning  schedules of energy generation and consumption.